Effectiveness and complications of ossiculoplasty in a tertiary care hospital of North East India - Kakati, Arup; Singh, Yashdeep (International Journal of Research in Medical Sciences, 2024)
Chronic otitis media is the leading acquired cause of hearing impairment which may be due to ossicular erosion. Restoration of ossicular chain continuity using autografts and allografts along with tympanoplasty can improve some degree of hearing with limited complications. Institution based prospective study was done on 20 patients diagnosed with chronic otitis media and history of trauma enrolled in the department of ENT and head and neck surgery, GMCH-Guwahati from July 2023-June 2024 to analyse the effectiveness and complications of ossiculoplasty using various autografts and allografts. After 3 months A-B gap was reduced in all the patients who were included in the post- operative follow- up but no significant difference could be elicited in the effectiveness of autografts and allografts. Extrusion of TORP was noted in 1 patient; 1 patient’s graft uptake was not complete which concludes that ossiculoplasty improves the hearing and the risk benefit ratio of complications and quality of life is favourable.